Methods of treatment of eating disorders according to behavioral nutrition (Research, Society and Development, 2023)
Methods for treating eating disorders according to Behavioral Nutrition. Objective: to evaluate the effectiveness of behavioral nutrition in the treatment of eating disorders, more specifically anorexia, bulimia and binge eating disorder, analyzing the techniques used and their effects on individuals with it. Methodology: the method used was descriptive, carried out based on a bibliographic review, carried out through books and articles published in electronic databases between 2007 and 2022, using Google Scholar and Pubmed as databases. Final considerations: behavioral nutrition presents effective techniques for adequate and lasting treatment, especially in cases of anorexia and bulimia nervosa, and binge eating. However, it is necessary for the nutritional therapist to be well trained to apply them, respecting the individualities of each patient and investigating their progress so that they can continue using them. Furthermore, more research needs to be done to improve the treatment and conduct of nutritionists and other health professionals.